MODSSO - A Manager-centric Global Decision Support System for Organizations - Garrido, Paulo (2012)
The goal of this paper is to describe a set of structured concepts for the design of software systems supporting the global decision process in an enterprise or organization.The concepts has as elements: i) each manager has available a decision dashboard to support, in a framework of decision theory, the flux of decision-making for which he or she is responsible; ii) the dashboards also allow managers crowdsourcing from non-managers different aspects of decision iii) the dashboards are connected in a conversational network; iv) this conversational network is so structured to support the global decision process of the organization. An example of implementation's architecture for the concept will be described.